Structure Properties, Acquisition Protocols, and Biological Activities of Oleuropein Aglycone - Xu, Fangxue; Li, Yujuan; Zheng, Mengmeng; Xi, Xiaozhi; Zhang, Xuelan; Han, Chunchao (Frontiers in Chemistry, 2018)
Oleuropein aglycone, which is the major phenolic component of extra virgin olive oil, is becoming increasingly popular and important in scientific and public communities. This paper summarizes the structure properties, acquisition protocols and biological activities of oleuropein aglycone. There are three kinds of hydrolytic ways to obtain oleuropein aglycone from oleuropein: including enzymatic hydrolysis, acid hydrolysis and acetal hydrolysis. Enzymatic hydrolysis can be achieved by exogenous enzymes and endogenous enzymes. In addition, the diverse pharmacological effects of oleuropein aglycone are summaried. These pharmacological effects include anti-Alzheimer’s disease, anti-breast cancer, anti-inflammatory, anti-hyperglycemic, anti-oxidative, and lipid-lowering properties. Therefore, we can use hydrolysis and biological activities to study oleuropein aglycone in the future.